2015
DOI: 10.1155/2015/604658
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Oxidative Stress-Induced Epigenetic Alterations in Amyloid-βProduction in Alzheimer’s Disease

Abstract: An increasing number of studies have proposed a strong correlation between reactive oxygen species (ROS)-induced oxidative stress (OS) and the pathogenesis of Alzheimer's disease (AD). With over five million people diagnosed in the United States alone, AD is the most common type of dementia worldwide. AD includes progressive neurodegeneration, followed by memory loss and reduced cognitive ability. Characterized by the formation of amyloid-beta (Aβ) plaques as a hallmark, the connection between ROS and AD is co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
86
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(88 citation statements)
references
References 148 publications
2
86
0
Order By: Relevance
“…Several recent review studies have reported that extracellular Aβ causes oxidative stress to the mitochondria, which thus leads to its inevitable dysfunction [11,12]. Additionally, in vivo studies have also reported that Aβ is highly linked to mitochondrial structural abnormalities, as it was found to accumulate within mitochondria in the brains of AD patients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Several recent review studies have reported that extracellular Aβ causes oxidative stress to the mitochondria, which thus leads to its inevitable dysfunction [11,12]. Additionally, in vivo studies have also reported that Aβ is highly linked to mitochondrial structural abnormalities, as it was found to accumulate within mitochondria in the brains of AD patients [13,14].…”
Section: Introductionmentioning
confidence: 99%
“…Reactive oxygen species are involved in many diseases, including neurological diseases (Zuo et al, 2015b), heart failure (Zuo et al, 2015a) and hypertension (Zuo et al, 2014b). A large number of studies have shown that ischemic postconditioning can significantly reduce ROS production, thereby reducing myocardial I/R injury (Barsukevich et al, 2015; Singh et al, 2012; Zhao et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Aβ accumulation in the brain and in cerebral blood vessels causes neurotoxicity by directly inducing oxidative stress [79] and by indirectly promoting microglia activation [80]. Aβ accumulation in blood vessels can impair also the blood-brain barrier (BBB) [81], exacerbating the disease progression.…”
Section: Alzheimer's Diseasementioning
confidence: 99%